Penerapan Strategi Pembelajaran Mind Map Untuk Meningkatkan Hasil Dan Aktivitas Belajar Siswa Pada Materi Pokok Struktur Dan Fungsi Jaringan Tumbuhan Di Kelas VIII-A SMP Negeri 4 Jakarta - Sunita Siskawati Pane (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research aims to find out whether the application of the Mind map learning model to the main topic of structure and function of tissues in plants can improve student learning outcomes. This research is a PTK carried out in two cycles, each consisting of two meetings. This is intended to obtain maximum research results.From the implementation of this PTK, findings were obtained that there was an increase in learning outcomes and student activities. This can be seen from the results of observations in cycle I and cycle II. In the first cycle, students' test scores averaged 65.79 with student activity increasing from 27% to 43%, while student learning completion was only 65.79%. In cycle II, students' test results increased to an average of 72.10, their activities also increased from 49% to 69%, while students' learning completion reached 74.38%.From the overall data and findings, it can be concluded that the application of the Jigsaw learning model to Mind map learning material on the main topic of structure and function of tissues in plants can improve the learning outcomes of class VIII.A students at SMP Negeri 4 Jakarta.